Psychopathology : history, diagnosis, and empirical foundations - Craighead, W. Edward; Miklowitz, David Jay, 1957-; Craighead, Linda W. (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
"Designed for graduate level courses in adult psychopathology, the Second Edition of this book incorporates the newly released (2013) DSM-5 . Unique in its approach, this text presents a historical context in which current diagnoses are made. Presenting an overview of the issues and methodologies of conducting assessments, each of the major psychological disorders is discussed in a standard format in the chapter dealing with that disorder. The text includes new chapters on nonalcohol substance abuse and contextual factors affecting diagnoses. Each chapter covers: description from DSM, using case examples; epidemiology; basic research, including neurobiology and neuroscience of the disorder; prevalence and consequences of the disorder; behavioral, social, cognitive, and emotional aspects of the disorder; and treatment of the disorder, using clinical examples showing how psychopathology and assessment influence treatment"--
Machine generated contents note: Chapter 1: Issues in Diagnosis: Conceptual Issues and ControversiesScott O. Lilienfeld, Sarah Francis Smith and Ashley L. WattsChapter 2: Strategies for Evidence-Based Assessment of Children and Adolescents: Measuring Prediction, Prescription, and ProcessEric A. Youngstrom and Thomas W. FrazierChapter 3: Obsessive-Compulsive DisorderJonathan S. Abramowitz, Laura E. Fabricant, and Ryan J. JacobyChapter 4: Generalized Anxiety DisorderKaren Rowa, Heather K. Hood, and Martin M. AntonyChapter 5: Social Anxiety DisorderDeborah Roth Ledley, Brigette A. Erwin, Amanda S. Morrison, and Richard G. HeimbergChapter 6 Panic DisorderJoanna J. Arch, Lauren N. Landy and Michelle G. CraskeChapter 7: Posttraumatic Stress DisorderPatricia A. Resick, Candice M. Monson, and Shireen L. RizviChapter 8: Major Depressive DisorderLorie A. Ritschel, Charles F. Gillespie, Eir?ikur ?O. Arnarson, and W. Edward CraigheadChapter 9: Dysthymia and Chronic DepressionDaniel N. Klein and Sarah R. BlackChapter 10: Bipolar DisordersDavid J. Miklowitz and Sheri L. JohnsonChapter 11: Schizophrenia and the Psychosis SpectrumHanan D. Trotman, Vijay Mittal, Kevin Tessner, and Elaine F. WalkerChapter 12 Bulimia Nervosa and Binge Eating DisorderLinda W. Craighead, Margaret Martinez, and Kelly L. KlumpChapter 13 Eating Disorders: Anorexia NervosaJAMES LOCK AND NINA KIRZChapter 14: Borderline Personality DisorderJill M. Hooley and Sarah A. St. GermainChapter 15: Alcohol Use DisordersLara A. Ray, Kelly E. Courtney, and Guadalupe BacioChapter 16: Psychopathy as psychopathology: Key developments in assessment, etiology, and treatmentJennifer E. Vitale and Joseph P. NewmanChapter 17: Sexual DysfunctionCindy M. Meston and Carey S. PulvermanChapter 18: Sleep DisordersJennifer C. Kanady and Allison G. Harvey.
Includes bibliographical references and index.
Mode of Access: World Wide Web
Keywords: Mental Disorders -- diagnosis; Mental Disorders -- classification; Psychopathology -- methods; Electronic books